Measurement of Electromagnetic Field Component Emissions as a Precursor of Emerging Hazard in Coal Mines - Remigiusz Mydlikowski; Krzysztof Maniak (Journal of Telecommunications and Information Technology, 2019)
The article presents the results of research concerning electromagnetic (EM) ﬁeld emitted by rocks during the process of their destruction. The paper describes a measuring stand designed for subjecting rock samples to axial crushing. During the destruction of rock samples, both components of the electromagnetic ﬁeld emitted by the rock were recorded. The paper presents the results of research on hard coal samples, presenting the obtained time domain waveforms and frequency spectrum of the emitted EM ﬁeld components. Further potential uses of tests concerned with EM emitted by rocks are determined. Applications registering EM ﬁeld in mine environments may provide an early mine collapse warnings.